Glycyrrhizin attenuates rat ischemic spinal cord injury by suppressing inflammatory cytokines and HMGB1 - Gong Gu; Yuan Li-bang; Hu Ling; Wu Wei; Yin Liang; Hou Jing-li; Liu Ying-hai; Zhou Le-shun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the neuroprotective effect of glycyrrhizin (Gly) against the ischemic injury of rat spinal cord and the possible role of the nuclear protein high-mobility group box 1 (HMGB1) in the process. Methods: Male Sprague-Dawley rats were subjected to 45 min aortic occlusion to induce transient lumbar spinal cord ischemia. The motor functions of the animals were assessed according to the modified Tarlov scale. The animals were sacrificed 72 h after reperfusion and the lumbar spinal cord segment (L2–L4) was taken out for histopathological examination and Western blotting analysis. Serum inflammatory cytokine and HMGB1 levels were analyzed using ELISA. Results: Gly (6 mg/kg) administered intravenously 30 min before inducing the transient lumbar spinal cord ischemia significantly improved the hind-limb motor function scores, and reduced the number of apoptotic neurons, which was accompanied by reduced levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in the plasma and injured spinal cord. Moreover, the serum HMGB1 level correlated well with the serum TNF-α, IL-1β and IL-6 levels during the time period of reperfusion. Conclusion: The results suggest that Gly can attenuate the transient spinal cord ischemic injury in rats via reducing inflammatory cytokines and inhibiting the release of HMGB1.